Efficiency and competitiveness of Malaysian processed palm oil industry - Shahverdi, Zahra (2013)
Malaysia as the dominant producer and exporter of processed palm oil (PPO) in the world, has experienced very sharp decrease in its market share from 93.8% in 1989 to 67% in 2009. Furthermore, the difference between the average price of crude palm oil (CPO) and PPO in the world market has decreased considerably. Therefore, competitiveness of this industry in the world market is doubtful. Hence, this study investigates the source of the decrease in competitiveness of Malaysian palm oil refining industry during 1989 to 2009 by looking at the efficiency of the industry as a performance index. Here we apply 2-stage data envelopment analysis (DEA) approach with variable returns to scale (VRS) assumption on a sample comprises 27 out of 51 actively operating refineries in Malaysia in 2010.We apply the data from our sample to investigate the impact of six different factors on the inefficiency of the refineries, by applying Banker‟s test statistics in 1993 & 1995 on inefficiency scores based on Banker, Charnes and Cooper (BCC) model, to find solutions for increasing the efficiency, and as a result, the competitiveness of Malaysian PPO in the world market. Since trade liberalization is inevitable in the long run, its impact on the refineries‟ competitiveness in the world market will be one of the main future concerns of the country. Therefore we apply dominant firm- competitive fringe market structure model on data from 1989 to 2009 and then simulate our model under free trade over the same period to find the effect of trade liberalization on competitiveness of this industry. The results show decreasing technical efficiency between 1996 and 2009, and low levels of cost and allocative efficiency over the same period. We also find out that vertical integration and involvement of foreign investors have increased inefficiency. Joint ventures between private firms and government tends to be less inefficient, and refineries in peninsular Malaysia are more inefficient than those located in Sabah and Sarawak. These could be due to the CPO tax cut in Sabah and Sarawak that leads to decrease inefficiency of the refineries in 2001 and 2002. Briefly, this study shows that inefficiency in Malaysia‟s refineries during 1996-2009 was mostly related to spare capacity of them, which was due to any reason that increased the CPO price or decreased the difference between CPO and PPO prices.Besides, trade liberalization appears to result in a small reduction in market power of Malaysia refining industry in the world market because of new entrances and more production costs that poses competition to the Malaysia refined palm oil industry.